Allelopathic potential of Bothriochloa laguroides var. laguroides (DC.) Herter (Poaceae: Andropogoneae) - Scrivanti, Lidia Raquel (2010)
Bothriochloa laguroides var. laguroides (DC.) Herter, a native bluestem of America, has been shown to produce many biologically active compounds. The allelopathic potential of aqueous extracts from roots, stems and leaves was examined. Lettuce seeds (Lactuca sativa) and maize (Zea mays), the common allelopathy bioassay systems, as well as seeds from two native species, wintergreen paspalum (Paspalum guenoarum) and lovegrass (Eragrostis curvula), were germinated in the presence of aqueous extracts. Percent seed germination, root and shoot elongation were measured. After 4 and 7 days root, stem and leaf extracts caused inhibition of root and shoot elongation in all four species tested. Aqueous extracts were generally less inhibitory to seed germination. Aqueous extracts from different parts of B. laguroides var. laguroides show therefore allelopathic effects inhibiting, in particular, growth of competing plants.